2023
DOI: 10.3390/antibiotics12020291
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Antimicrobial Susceptibility Characterization of Escherichia coli Isolates from Bovine Slaughterhouse Process

Abstract: Antimicrobials are routinely used in human and veterinary medicine. With repeated exposure, antimicrobials promote antibiotic resistance, which poses a threat to public health. In this study, we aimed to determine the susceptibility patterns, virulence factors, and phylogroups of E. coli isolates during the killing process in a bovine slaughterhouse. We analyzed 336 samples (from water, surfaces, carcasses, and feces), and 83.3% (280/336) were positive for E. coli. The most common phenotypic resistances that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
1
Order By: Relevance
“…was detected in none of them. The prevalence data for E. coli are lower than those obtained by other authors in pig (35.1%) [33] and bovine (41.6%) [34] slaughterhouses but higher than those found in lamb slaughterhouse surfaces (4.2%) [35].…”
Section: Isolation and Identification Of Microorganismscontrasting
confidence: 77%
“…was detected in none of them. The prevalence data for E. coli are lower than those obtained by other authors in pig (35.1%) [33] and bovine (41.6%) [34] slaughterhouses but higher than those found in lamb slaughterhouse surfaces (4.2%) [35].…”
Section: Isolation and Identification Of Microorganismscontrasting
confidence: 77%
“…All five isolates identified as UPEC were grouped into phylogroup D and isolates within this group are considered of risk to public health ( Orsi et al, 2007 ; Vázquez-Villanueva et al, 2023 ). While other studies reported that the predominant phylogroup in UPEC isolated from Europe and elsewhere is B2, followed by D ( Dubois et al, 2010 ; Ejrnæs et al, 2011 ; Halaji et al, 2022 ), no isolate of phylogroup B2 was identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The mdh gene was employed to confirm the identification of E. coli as described by Vasquez et al [ 42 ]. All strains that were confirmed to be E. coli were subjected to the phenotypic screening of ESBL production using the double-disk synergy test according to the European Committee on Antimicrobial Susceptibility Testing guidelines [ 43 ].…”
Section: Methodsmentioning
confidence: 99%